Metabolic and reproductive characteristics of first-degree relatives of women with self-reported oligo-amenorrhoea and hirsutism. - Torvinen, A; Koivunen, R; Pouta, A; Franks, S; Martikainen, H; Bloigu, A; Hartikainen, A; McCarthy, M; Ruokonen, A; Järvelin, MR; Morin-Papunen, L (2011)
OBJECTIVE: To investigate the occurrence of oligo-amenorrhoea and hirsutism, infertility and metabolic morbidity among first-degree relatives of women with and without self-reported oligo-amenorrhoea and hirsutism. DESIGN: Nested case-control study. SETTING, POPULATION AND METHODS: A postal questionnaire about symptoms of oligo-amenorrhoea and hirsutism was sent to all women of the Northern Finland Birth Cohort 1966 (n = 5889). From this population were randomly selected 98 women with both symptoms and 163 without symptoms. A further questionnaire on the occurrence of oligo-amenorrhoea, hirsutism, infertility, early balding and metabolic morbidity in their relatives was sent to this subpopulation. MAIN FINDINGS: We obtained data on 183 relatives of 43 women with symptoms and 412 relatives of 86 symptomless women. Compared with relatives of symptomless women, mothers of women with symptoms suffered significantly more often from hirsutism and menstrual disorders, and sisters more often from hirsutism and infertility, and had fewer children and were more often childless. There was an increased prevalence of diabetes in the sisters and of hypertension in the fathers of women with symptoms. CONCLUSIONS: These results strengthen earlier findings of significantly increased metabolic and reproductive morbidity in the relatives of women with symptoms of PCOS.